Ensino de biologia contextualizado na astronomia: contribui??es da expografia de microrganismos extrem?filos - Oliveira, Rodrigo de Queiroz (2024)
Astrobiology emerges as a fascinating area of scientific research. It creates an interdisciplinary environment for teaching, learning and dissemination about the origin, evolution, distribution and future of life on Earth and beyond. In Basic Education, Astrobiology is included in the National Common Curricular Base (BNCC) and functions as an integrating axis of knowledge, articulating the curricular components of Biology, Physics and Chemistry. Therefore, in this exploratory study, with a qualitative approach, complemented with a quantitative one, the objective was to enable an understanding of the search for life in extraterrestrial environments similar to Earth. To this end, the methodology adopted consisted of mobilizing students from a class of the Technical Course in Chemistry Integrated to High School at a public school in debate, conversation circles, visits to science museums, composition of a poem, observation of celestial bodies and workshops for conception, assembly and monitoring of an exhibition on extremophile microorganisms as models for the search for life beyond Earth. For data analysis, Discourse Analysis, Content Analysis, Collective Subject Discourse technique and Cronbach's alpha coefficient were adopted. The results indicate that the debate promoted processes of argumentation and consensus that life exists outside Earth; the questions in the conversation circles involved how science, technology and innovation in astronomy can impact everyday life; visits to science museums provided opportunities for scientific, cultural and socializing learning; the poem composition demonstrated the appropriation of astronomical content and the creation of imaginative bridges driven by emotion; observation of celestial bodies has produced evidence of astrobiological targets; the workshops demonstrated the most recent model for the origin of life and the search for it beyond Earth; the exhibition enabled a meeting between the visitor and the exhibition group covering Astrobiology; and participation in events constituted a strategy for scientific initiation, dissemination and popularization of Astrobiology. Furthermore, 87.5% of students completely agree that the transposition of a scientific model to a didactic model of the possible existence of life on Jupiter's moon Europa proposes acquiring knowledge about the origin of life. This data suggests that the school is a privileged space to articulate and deepen the recent knowledge provided by Astrobiology and the Professional Master's in Teaching enables this dialogical articulation between teacher and student and scientists. It is concluded that the design, assembly and evaluation of the expography contributed to the dissemination and popularization of Astrobiology by articulating scientific and cultural content for the interdisciplinary understanding of the search for life in extraterrestrial environments analogous to Earth. Through this study, the e-books ?Didactic sequence for teaching and learning Astrobiology?, ?Conversation circles with students about Astrobiology?, ?Booklet of summaries and posters of scientific works on Astrobiology presented at events? and ?Astrobiology Exhibition goes to School?, as educational products to be used by professionals involved in teaching.